Choosing pacemakers appropriately - Panicker, G K (Heart Asia, 2009)
The range of implantable cardiac pacing devices has expanded, with the advances in available technology. Indications for cardiac pacing devices, that is pacemakers, implantable cardioverter defibrillators (ICDs) and cardiac resynchronisation therapy devices (CRTs), have expanded for the treatment, diagnosis and monitoring of bradycardia, tachycardia and heart failure. While the need for pacemakers is increasing, not all patients who require pacemakers are receiving them, especially in the Asia-Pacific region. There is a need to be more critical in advising the use of more expensive devices like ICDs and CRT/CRT-D devices, since most patients in the Asia-Pacific region pay out of pocket for these therapies. The AHA-ACC guidelines need not be blindly followed, since they are too wide-sweeping and are often based on the intention-to-treat basis of trials rather than on the parameters of the patients actually enrolled.